2015
DOI: 10.4236/oalib.1101799
|View full text |Cite
|
Sign up to set email alerts
|

The Comparison of Clinical and Biochemical Outcomes in Off-Pump and Conventional Coronary Artery Bypass Grafting Surgery

Abstract: Objective: There is no common concencus the clinical results of coronary artery bypass grafting (CABG) surgery patients who underwent off-pump or conventional techniques. Our aim of this study was to compare the changes of myocardial functions, patients' clinical results, biochemical marker release during surgery and postoperatively in On-and Off-Pump CABG surgery. Method: A consecutive series of 50 coronary artery disease (CAD) patients who underwent elective CABG surgery included for this study. The patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In Hussain et al study (2016) the postoperative elevation of CK-mb displayed as mean ± SD was 57.69 ± 38.57 IU/L in on-pump group, while it was 30.27 ± 21.85 IU/L, (P-value < 0.001). 8 Moreover, Temizturk et al (2015) reported that troponin release was calculated at 4 hours; it was 5.78 ± 5.61 in on-pump group and 0.49 ± 0.27 ng/ml in offpump group (P-value < 0.001). At 8 hours, this value was measured as 6.58 ± 7.97 in on-pump group and 0.65 ± 0.34 ng/ml in off-pump group (P-value < 0.001).…”
Section: Postoperative Datamentioning
confidence: 99%
See 1 more Smart Citation
“…In Hussain et al study (2016) the postoperative elevation of CK-mb displayed as mean ± SD was 57.69 ± 38.57 IU/L in on-pump group, while it was 30.27 ± 21.85 IU/L, (P-value < 0.001). 8 Moreover, Temizturk et al (2015) reported that troponin release was calculated at 4 hours; it was 5.78 ± 5.61 in on-pump group and 0.49 ± 0.27 ng/ml in offpump group (P-value < 0.001). At 8 hours, this value was measured as 6.58 ± 7.97 in on-pump group and 0.65 ± 0.34 ng/ml in off-pump group (P-value < 0.001).…”
Section: Postoperative Datamentioning
confidence: 99%
“…These measurements were significantly different when compared to both groups. 9 Consequently, this elevation may correlate with intraoperative myocardial injury related to pericardium manipulation, cardiac manipulation, inadequate myocardial protection during bypass time, intraoperative defibrillation, or acute post-bypass hemodynamic instability .…”
Section: Postoperative Datamentioning
confidence: 99%